CHALLENGES IN REGULATION AND OPPORTUNITIES IN SHARIA FINANCIAL MANAGEMENT - Hamizar, Arizal; Tubalawony, Jacsy; Yaman, Afdhal; Kamaruddin (PT. Intelek Cendikiawan Nusantara, 2024)
This research aims to explore the fundamental concepts of Islamic finance management, its principles, sources of funding, as well as Sharia financial products and innovations available from a theoretical perspective based on related literature. The study also discusses the changing global economic context, the complexity of Sharia financial regulations and standards, and the challenges and opportunities faced in the development of products, human resource education, and social and environmental responsibilities. The research findings indicate that Islamic finance management faces complex challenges and opportunities in dealing with the current dynamics of the global economy. The adoption of information technology and digital innovation has opened up new opportunities to enhance accessibility, operational efficiency, and customer experience in the Islamic finance industry. However, challenges such as regulatory complexity and standards, as well as the need for skilled human resources in Islamic economic principles, remain a primary focus in ensuring the growth and sustainability of the Islamic finance industry.